The Role of Islamic Higher Education Insitutions in Preventing Radicalism of Thought in Indonesia, Malaysia, and Thailand - Harahap, Syahrin; Yamamah, Anshari; Harahap, Sholahuddin; Chaphakia, Ahmad Omar (Edudeena : Journal of Islamic Religious Education, 2025)
The phenomenon of ideological radicalism among university students poses a serious challenge to social stability and national integration. Islamic Higher Education Institutions are positioned as the frontline in shaping students’ moderate and tolerant thinking. However, field observations show that some institutions are vulnerable to the spread of radical ideologies. This study aims to analyze the understanding of radicalism that emerges and the role of Islamic educational institutions in addressing radicalism. The research employs a socio-philosophical approach to gain a deeper and more comprehensive understanding of the social phenomenon. This is a library research study using sources from national and international journal articles as well as other supporting data. The data analysis technique applied is narrative analysis. The results indicate that radicalism in Indonesia, Malaysia, and Thailand can be divided into two forms: true radicalism and potential radicalism. This is caused by three factors: (1) internal factors, including destructive tendencies within individuals; (2) external factors, such as socio-political pressures; and (3) cultural factors, including rejection of secularism. Islamic Higher Education Institutions have a role in minimizing radicalism through two approaches: (1) structural approaches, including conducting inter-campus dialogues, supervising academic processes, and establishing radicalism prevention bodies within campuses; and (2) cultural approaches, such as curriculum reformulation/adaptation, syllabus reorientation, and reorientation of the tridharma (three main duties) of higher education institutions.